Conceptual Pathways to Ethnic Transcendence in Diverse Churches: Theoretical Reflections on the Achievement of Successfully Integrated Congregations - Marti, Gerardo (Religions, 2015)
The concept of ethnic transcendencedefined as the process of co-formulating a shared religious identity among diverse members that supersedes their racial and ethnic differences through congregational involvementcaptures a critical aspect of successfully integrating different racial and ethnic groups into a single, commonly shared, multi-ethnic congregation. Drawing on classic theoretical resources from Max Weber and Emile Durkheim, this paper expands on previous scholarship by conceptually articulating two different paths for the achievement of ethnic transcendence in multiracial congregations. In the first path, ethnic transcendence supports and encourages congregational diversification by inspiring members and mobilizing them to contribute their efforts to accomplish a common religious mission. In the second path, the achievement of ethnic transcendence involves the sublimation of congregational members' religious selves to an overarching moral collective. Both paths involve privileging religious identities in favor of a particularistic ethnic or racial identity. Moreover, through both paths, the development of congregationally specific religious identities results in joining with co-members of different ethno-racial ancestries as a type of spiritually-derived kinship. Due to the fact that ethnic transcendence is an interactive process, congregational diversity is a bi-directional phenomenon representing the extent to which members allow for the integration of separate ethnicities/races into a common congregation through idealized and richly-symbolic notions of connection and belonging to a congregation. Overall, this paper suggests a heuristic framework that productively expands the concept of ethnic transcendence, allows an approach for observing cross-ethnic/inter-racial organizational processes, and ultimately contributes toward understanding how congregations (whether church, temple, or mosque) pursue alternative identity reconstruction projects to sustain cohesive collective identities.